2003
DOI: 10.1034/j.1399-6576.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to the prone position in spontaneously breathing patients with hypoxemic respiratory failure

Abstract: The prone position may prove beneficial in some cases of hypoxemic respiratory failure, even in awake patients, by avoiding mechanical ventilation and ventilator-associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 10 publications
1
94
0
3
Order By: Relevance
“…The observation by Valter et al (2003) is of interest. This is the only study, identified in this literature search, which used PP on awake and spontaneously breathing patients as treatment for hypoxaemic respiratory failure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The observation by Valter et al (2003) is of interest. This is the only study, identified in this literature search, which used PP on awake and spontaneously breathing patients as treatment for hypoxaemic respiratory failure.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been noted during this literature review that nearly all studies on the effect of PP have only included participants with an already established ARDS. Only one study using PP in awake and spontaneously breathing patients as treatment for hypoxaemic respiratory failure in which mechanical ventilation was indicated (Valter et al, 2003) was identified. In a case study of four patients, Valter et al (2003) turned the patients to PP while being awake and breathing spontaneously.…”
Section: Prone Positioningmentioning
confidence: 99%
“…Accordingly, in the presented study, the slope of the V R gradient is less steep at the second measurement in both positions due to increased hypoventilation compared with the first measurement, which is supported by the trend of more pronounced differences between the two measurements in the gravitationally dependent lung regions preferably in the supine position measurement. The more stable gradient of the prone position is associated with an improved ventilation (oxygenation) in the prone position, which is in concordance with the fact that the prone position is commonly used in intensive care unit in patients with respiratory failure …”
Section: Discussionmentioning
confidence: 99%
“…Hypoventilated regions seemed to be reduced in the prone position ( Figure 7). As discussed in previous publications, 44,45 one would assume that the amount of tissue subjected to hypoventilation/atelectasis is the same in the supine and prone positions. However, Tobin and Kelly 46 reported that there are different amounts of compression of the dependent lung regions by the mediastinum and heart in the prone versus the supine position, which leads to less pronounced hypoventilation in dependent parts of lungs in the prone position.…”
Section: Anterior-posterior Gradient Of Ventilationmentioning
confidence: 99%
“…Reports of the application of PP in spontaneously breathing, non-intubated adult patients are limited to few case reports [15][16][17].…”
Section: Introductionmentioning
confidence: 99%